Crop Tree Management Improved Growth and Crown Class Maintenance of Green Ash: 18-Year Results - A. E. Houston; W. K. Clatterbuck; J. L. Bowers (Forest Science, 2026)
A crop tree management study targeting green ash ( Fraxinus pennsylvanica Marsh.) was established in a 16-year-old, naturally regenerated, mixed-species, bottomland hardwood stand in southwest Tennessee. The goal was to maintain or improve ascendance of green ash into the overstory of a developing stand that otherwise might not occur. Three treatments were examined: a complete crown-touching release; the same release treatment along with a one-time, fertilizer application; and a control. Initial diameters, heights and crown size parameters were measured in 1996 and 18 years later. The two release treatments did not differ significantly in diameter and height growth response, but statistically outperformed the control treatment. Similarly, crown class scores did not differ between the two release treatments, but were significantly improved from the control. Both release treatments displayed a greater percentage of crop trees successfully competing for upper canopy status compared to the control. Using initial tree diameter as a reflection of crown size and position of crop trees, diameters of 12.5 to 20 cm were more likely to be a component of the overstory 18 years following crop tree treatments. Crop trees less than 12.5 cm in diameter were likely to remain in the subordinate crown classes. Trees greater than 20 cm in diameter were already in the overstory and maintained their upper canopy position. These results suggest that crop tree management can be an effective management tool for improving growth as well as improving overstory presence of green ash in pole-sized, mixed-species, bottomland hardwood stands.